Decolonizing Christian Education in Batak: Initiating Curriculum Transformation - Herman Tampubolon; Izak Y. M. Lattu; Mariska Lauterboom; Tony Tampake (Newinera Publisher, 2026)
This article examines the enduring colonial legacy within Christian education in the Batak region, which has systematically marginalized indigenous knowledge and privileged Western pedagogical paradigms as the normative expression of Christianity. Focusing on the Sunday School ministry of the Huria Kristen Indonesia (HKI) church, the study initiates a critical inquiry into curriculum transformation through the lens of decolonial theory. Employing an interdisciplinary methodology that integrates the sociology of education, sociology of religion, and decolonial studies, qualitative data were gathered through in-depth interviews with two pastoral practitioners and contextual observations. The Batak philosophy of Sala Mandasor Sega Luhutan (SMSL) serves as a critical framework to deconstruct entrenched Eurocentric curricula and reconstruct pedagogical practices that center indigenous epistemology. Findings reveal that despite HKI’s historical resistance to missionary hegemony, its Sunday School curriculum remains dominated by hierarchical, banking-model pedagogy that treats children as passive recipients. Indigenous cultural elements are largely confined to ceremonial performances rather than substantive instructional integration, perpetuating epistemic alienation and dehumanization. The study argues that authentic decolonization requires pastors and educators to transition toward dialogical, problem-posing methodologies that recognize Sunday School children as active epistemic subjects bearing the imago Dei. By embedding Batak kinship values, oral traditions, and symbolic frameworks into core biblical instruction, Christian education can become a liberating practice that honors cultural heritage while fostering theological contextualization. This research offers a strategic pathway for ecclesiastical curriculum reform ahead of HKI’s centenary in 2027.